1998
DOI: 10.1016/s0378-4371(97)00476-7
|View full text |Cite
|
Sign up to set email alerts
|

Interfaces and grain boundaries of lamellar phases

Abstract: Interfaces between lamellar and disordered phases, and grain boundaries within lamellar phases, are investigated employing a simple Landau free energy functional. The former are examined using analytic, approximate methods in the weak segregation limit, leading to density profiles which can extend over many wavelengths of the lamellar phase. The latter are studied numerically and exactly. We find a change from smooth chevron configurations typical of small tilt angles to distorted omega configurations at large… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 10 publications
2
19
0
Order By: Relevance
“…Twist grain boundaries in the lamellar phase have been investigated within self-consistent field theory for diblock copolymers 28 and observed experimentally 29 to have a structure similar to Scherk's minimal surface. Tilt grain boundaries in the lamellar phase, where the normals of the lamellae of the two grains define a plane perpendicular to the boundary, have been shown within a Ginzburg-Landau theory to be chevron-shaped at small tilt angles and omega-shaped at large tilt angles, 22,27 in agreement with experimental results. 30 The nucleation of defects in the gyroid cubic mesophase has recently been observed in Lattice-Boltzmann simulations.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Twist grain boundaries in the lamellar phase have been investigated within self-consistent field theory for diblock copolymers 28 and observed experimentally 29 to have a structure similar to Scherk's minimal surface. Tilt grain boundaries in the lamellar phase, where the normals of the lamellae of the two grains define a plane perpendicular to the boundary, have been shown within a Ginzburg-Landau theory to be chevron-shaped at small tilt angles and omega-shaped at large tilt angles, 22,27 in agreement with experimental results. 30 The nucleation of defects in the gyroid cubic mesophase has recently been observed in Lattice-Boltzmann simulations.…”
Section: Introductionsupporting
confidence: 77%
“…In amphiphilic systems many kinds of interfaces occur: between two ordered phases, between ordered and disordered phases, and between two grains of the same ordered phase which differ by their spacial orientation. Recently, interfaces between coexisting lamellar, hexagonal, and disordered phases, [21][22][23] interfaces between lamellar and gyroid phases, 24,25 dislocations in cubic phases, 26 and grain boundaries in the lamellar phase 22,27,28 have been studied. Twist grain boundaries are interfaces between two grains of the same phase which differ only by a rotation around an axis perpendicular to the grain boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming for simplicity 1d lamellar modulations that are symmetric around φ 0 = 0, we use for φ the single-mode ansatz φ(x) = φ 0 + φ q cos(q 0 x), where the spatial average of φ(x) for the symmetric case is φ 0 = φ = 0, and φ q is its modulation amplitude, while ρ(x) is taken without any spatial modulations and is equal to its spatial average, ρ 0 = ρ [43][44][45][46]. Taking a variation with respect φ q , it can be shown that for the most dominant mode, q = q 0 , its amplitude φ q satisfies:…”
Section: Bulk Propertiesmentioning
confidence: 99%
“…[21] Furthermore, interfacial properties between different coexisting phases have been investigated using a similar model. [22][23][24] In the above expression for the free energy F, the f-leaflet has a dominant wavenumber q* 0 ¼ 1= ffiffi ffi 2 p , and so has the y-leaflet with q* y ¼ ffiffiffiffiffiffiffiffiffiffiffi C=2D p . The modulation wavenumbers and amplitudes of the two monolayers coincide when D = C = 1 and the average compositions are the same.…”
Section: Modelmentioning
confidence: 99%